2020
DOI: 10.3390/genes11121415
|View full text |Cite
|
Sign up to set email alerts
|

The Reversion of cg05575921 Methylation in Smoking Cessation: A Potential Tool for Incentivizing Healthy Aging

Abstract: Smoking is the largest preventable cause of mortality and the largest environmental driver of epigenetic aging. Contingency management-based strategies can be used to treat smoking but require objective methods of verifying quitting status. Prior studies have suggested that cg05575921 methylation reverts as a function of smoking cessation, but that it can be used to verify the success of smoking cessation has not been unequivocally demonstrated. To test whether methylation can be used to verify cessation, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
0
17
1
Order By: Relevance
“…The Smoking Computerized Tomography (SCT) cohort was collected as part of a project whose purpose was to understand the relationship of sildenafil on pulmonary 28 . In this protocol, subjects who smoked at least 10 cigarettes per day and had a 5-pack year history of smoking were invited to complete a REDCap® administered prescreening interview to assess smoking history and study eligibility.…”
Section: Methodsmentioning
confidence: 99%
“…The Smoking Computerized Tomography (SCT) cohort was collected as part of a project whose purpose was to understand the relationship of sildenafil on pulmonary 28 . In this protocol, subjects who smoked at least 10 cigarettes per day and had a 5-pack year history of smoking were invited to complete a REDCap® administered prescreening interview to assess smoking history and study eligibility.…”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, the use of cg05575921 as a metric for change in smoking intensity permits the stable objective measurement of smoking intensity [17,19]. Recently, we have shown that changes in cg05575921 methylation in response to smoking cessation are also dosedependent [16]. Therefore, in order to determine whether the changes in smoking intensity were related to the changes in methylation, we analyzed the relationship of the change of methylation at each of the cardiac markers to the change in smoking intensity as measured by change in cg05575921.…”
Section: Resultsmentioning
confidence: 99%
“…However, CHD prevention has no such social stigma, and recent work with biomarkers of hepatic injury has shown the benefit of physicians conveying similar information about the protective effects of alcohol cessation on liver function to patients with alcohol dependence [27]. Using potential effects of smoking cessation on CHD risk, alone or together with incentive-based programming methods for smoking cessation, could be a powerful motivator to persuade nicotine-dependent smokers to quit [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations